Opportunities to reduce pollination deficits and address production shortfalls in an important insect‐pollinated crop. Issue 8 (19th October 2021) - Garratt, Michael P. D.; de Groot, G. Arjen; Albrecht, Matthias; Bosch, Jordi; Breeze, Tom D.; Fountain, Michelle T.; Klein, Alexandra M.; McKerchar, Megan; Park, Mia; Paxton, Robert J.; Potts, Simon G.; Pufal, Gesine; et al.
Abstract: Pollinators face multiple pressures and there is evidence of populations in decline. As demand for insect‐pollinated crops increases, crop production is threatened by shortfalls in pollination services. Understanding the extent of current yield deficits due to pollination and identifying opportunities to protect or improve crop yield and quality through pollination management is therefore of international importance. To explore the extent of "pollination deficits, " where maximum yield is not being achieved due to insufficient pollination, we used an extensive dataset on a globally important crop, apples. We quantified how these deficits vary between orchards and countries and we compared "pollinator dependence" across different apple varieties. We found evidence of pollination deficits and, in some cases, risks of overpollination were even apparent for which fruit quality could be reduced by too much pollination. In almost all regions studied we found some orchards performing significantly better than others in terms of avoiding a pollination deficit and crop yield shortfalls due to suboptimal pollination. This represents an opportunity to improve production through better pollinator and crop management. Our findings also demonstrated that pollinator dependence varies considerably between apple varieties in terms of fruit number and fruit quality. We propose that assessments of pollination service and deficits in crops can be used to quantify supply and demand for pollinators and help to target local management to address deficits although crop variety has a strong influence on the role of pollinators.